Inositol 1,4,5-trisphosphate receptors in the heart - LAUREN MACKENZIE; H. LLEWELYN RODERICK; ANDREW PROVEN; STUART J CONWAY; MARTIN D BOOTMAN (Biological Research, 2004)
Inositol 1,4,5-trisphosphate (InsP3) is an established calcium-mobilizing messenger, which is well-known to activate Ca2+ signaling in many cell types. Contractile cardiomyocytes express hormone receptors that are coupled to the production of InsP3. Such cardioactive hormones, including endothelin, may have profound inotropic and arrhythmogenic actions, but it is unclear whether InsP3 underlies any of these effects. We have examined the expression and localization of InsP3 receptors (InsP3Rs), and the potential role of InsP3 in modulating cardiac excitation-contraction coupling (EC coupling). Stimulation of electrically-paced atrial and ventricular myocytes with a membrane-permeant InsP3 ester was found to evoke an increase in the amplitudes of action potential-evoked Ca2+ transients and to cause pro-arrhythmic diastolic Ca2+ transients. All the effects of the InsP3 ester could be blocked using a membrane-permeant antagonist of InsP3Rs (2-aminoethoxydiphenyl borate; 2-APB). Furthermore, 2-APB blocked arrhythmias evoked by endothelin and delayed the onset of positive inotropic responses. Our data indicate that atrial and ventricular cardiomyocytes express functional InsP3Rs, and these channels have the potential to influence EC coupling.